Identification of novel genetic variants associated with feline cardiomyopathy using targeted next-generation sequencing - Jade Raffle; Jose Novo Matos; Marsha Wallace; Lois Wilkie; Richard J. Piercy; Perry Elliott; David J. Connolly; Virginia Luis Fuentes; Androniki Psifidi (Scientific Reports)
Abstract Cardiomyopathies are the most common heritable heart diseases in cats and humans. This study aimed to identify novel genetic variants in cats with hypertrophic cardiomyopathy (HCM) and restrictive cardiomyopathy (RCM) using a targeted panel of genes associated with human cardiomyopathy. Cats were phenotyped for HCM/RCM by echocardiography ± necropsy. DNA was extracted from residual blood, and targeted next-generation sequencing was performed on two separate feline cohorts: an across-breed cohort (23 healthy cats and 21 HCM-affected pedigree or Domestic Shorthair cats), and a within-breed cohort of Birman pedigree cats (14 healthy, 8 HCM-affected, and 6 RCM-affected). Genome Analysis Toolkit was used for variant discovery. Genomic association analyses, including the covariates breed, age, and sex, were conducted to identify genetic variants of interest. We identified genetic variants associated with both HCM and RCM susceptibility in the sarcomeric genes ACTC1, ACTN2, MYH7, TNNT2 and the non-sarcomeric gene CSRP3 in the Birman pedigree cats. These findings suggest that, as proposed in humans, there is at least partial overlap in the genetic background between the HCM and RCM phenotypes in cats. These findings offer potential insights for comparative cardiac research and translational medicine.